2021
DOI: 10.3389/fneur.2021.699153
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early and Late Infarct Growth in DEFUSE 3

Abstract: Introduction: The goal of this study is to explore the impact of reperfusion and collateral status on infarct growth in the early and late time windows.Materials and Methods: Seventy patients from the DEFUSE 3 trial (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke) with baseline, 24-h, and late follow-up scans were evaluated. Scans were taken with DWI or CTP at time of enrollment (Baseline), with DWI or CT 24-h after enrollment (24-h), and with DWI or CT 5 days after enrollment (Late). Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Also, the population underlying the reference tractograms was not age‐matched to our sample of acute stroke patients. An important extension of the present work would be an analysis of the effects of thrombolysis on the trajectories of measures of brain network topology beyond 36 h. Since, in the absence of reperfusion treatment, infarcts have the potential to grow beyond 36 h (Christensen et al, 2019; Tate et al, 2021), the indirectly assessed connectivity‐preserving effect of thrombolysis might then be even larger. On the other hand, it is expected that secondary processes, including peri‐infarct selective neuronal loss and diaschisis, but also compensatory increases in connectivity, become more relevant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, the population underlying the reference tractograms was not age‐matched to our sample of acute stroke patients. An important extension of the present work would be an analysis of the effects of thrombolysis on the trajectories of measures of brain network topology beyond 36 h. Since, in the absence of reperfusion treatment, infarcts have the potential to grow beyond 36 h (Christensen et al, 2019; Tate et al, 2021), the indirectly assessed connectivity‐preserving effect of thrombolysis might then be even larger. On the other hand, it is expected that secondary processes, including peri‐infarct selective neuronal loss and diaschisis, but also compensatory increases in connectivity, become more relevant.…”
Section: Discussionmentioning
confidence: 96%
“…Since, in the absence of reperfusion treatment, infarcts have the potential to grow beyond 36 h (Christensen et al, 2019;Tate et al, 2021), the indirectly assessed connectivity-preserving effect of thrombolysis might then be even larger. On the other hand, it is expected that secondary processes, including peri-infarct selective neuronal loss and diaschisis, but also compensatory increases in connectivity, become more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Man et al also identified low collateral supply to be associated with lesion growth between baseline and follow-up at a sub-acute time point ( 11 ). However, in a subpopulation of the DEFUSE3 patients that received an unscheduled MRI or CT scan after 5 days, Tate et al found a statistically insignificant trend between good collateral circulation and larger lesion growth in the subacute period ( 30 ). Consistent with Campbell et al, they suggest that a better baseline collateral supply leads to a smaller lesion in the early time window, which can expand if the collaterals fail in the later time window, especially in patients with unsuccessful reperfusion ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the MR CLEAN trial, obtaining NCCT after 24 h and 1 week was standard practice unlike the DEFUSE 3 trial, which performed an unscheduled scan at 5 days only in the patients with a worse outcome. Studying collateral circulation in the subacute period would help to better understand the influence of collaterals on late lesion growth ( 14 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is plausible that a continuum of infarct severity exists that is more granular than the imaging based binary approach commonly used (i.e., tissue that is radiologically abnormal is uniformly damaged, while tissue that is radiologically normal is uniformly preserved) [46]. Conversely, if reperfusion is not achieved or is achieved late, infarct growth can continue beyond the 24-h period, leading 24-h scans to substantially underestimate final infarct size [50,51]. These dynamic changes in tissue state, potentially influenceable by distinct cerebroprotective agents, can only be visualized with serial imaging.…”
Section: Routine Acute Ischemic Stroke Imaging In Clinical Practice A...mentioning
confidence: 99%